प्रमिला गिरीका आधुनिक मूर्तिकलामा आध्यरूप : प्रघटनाशास्त्रीय सौन्दर्य अभिव्यक्ति (SIRJANĀ – A Journal Of Arts and Art Education, 2024)
Archetypal modern sculptures have been the medium of aesthetic expression of explicit observation. Objective of this study is to explore the contents and dialogues related to human values that are prevalent in the archetypal sculptures executed by Pramila Giri. The study is an attempt to analyze the aesthetic sense observed in the phenomenal archetype sculptures of the artist which are rooted with her individual experience, Nepali culture and knowledge. The study is qualitative, as well as based on individual perspectives. The study is focused on unveiling the differences between the classical form of the contemporary Nepali sculpture and the new aesthetic expressions.